2002
DOI: 10.1021/ja026280v
|View full text |Cite
|
Sign up to set email alerts
|

Investigations by 13C NMR Spectroscopy of Ethene-Initiated Catalytic CO Hydrogenation

Abstract: 13C NMR spectroscopy shows that the n-alkene and n-alkane products from the catalytic hydrogenation of CO in the presence of (13)C(2)H(4) probes over Ru/150 degrees C, Co/180 degrees C, Fe/220 degrees C, or Rh/190 degrees C (1 atm, CO:H(2) 1:1, "mild conditions") contain terminal (13)CH(3)(13)CH(2)- units. This is consistent with their formation by a regiospecific polymerization of C(1) species derived from CO and initiated by (13)C(2)H(4). Although the activities toward individual products differed somewhat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 76 publications
3
116
0
2
Order By: Relevance
“…In fact, whereas the addition of cyanide occurs at the carbyne carbon of 1a-c to form the alkylidene compounds [Fe 2 {µ-C(CN)N(Me)R}(µ-CO)(CO) 2 The MeCN ligand in 2a-c seems therefore able to direct selectively the nuclephilic attack at the metal atom. In order to determine whether this would apply to carbon nucleophiles such as organolithium or organocopper reagents, the reactions of 2a-c with LiR were studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, whereas the addition of cyanide occurs at the carbyne carbon of 1a-c to form the alkylidene compounds [Fe 2 {µ-C(CN)N(Me)R}(µ-CO)(CO) 2 The MeCN ligand in 2a-c seems therefore able to direct selectively the nuclephilic attack at the metal atom. In order to determine whether this would apply to carbon nucleophiles such as organolithium or organocopper reagents, the reactions of 2a-c with LiR were studied.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of complex 8 is the result of a nucleophilic attack at the coordinated NCCMe 3 , which presumably forms the azavinylidene intermediate [Fe 2 {µ-CN(Me)Xyl}(µ-CO)(CO){N=C(C≡CC 6 H 4 Me-4)CMe 3 } (Cp 2 )] (9). In spite of the fact that several azavinylidene complexes are known, 17 the intermediate 9 appears too unstable in our hands to be characterized even by spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under our conditions, incorporation is the most important reaction on both catalysts, which contrasts with ethene addition. Hydrogenation of ethene has been found to be the predominant conversion on both iron and cobalt catalysts [18][19][20] . Albert 21 studied ethylene and acetylene chemisorptions on Co(0001) and observed that an acetylene monolayer blocks all surface sites for subsequent CO chemisorptions, while an ethylene monolayer allows the coadsorption of 25% of a CO monolayer.…”
Section: Effect Of Operating Variables On Acetylene Incorporationmentioning
confidence: 99%
“…SEM and EDX analysis will also be used to identify the Pt components. Other materials, such as Y-zeolite 17 and especially amorphous silica-alumina 18 have been reported to produce transportation fuels from long-chain paraffins. Combining these materials with PtWZr catalysts may result in a hybrid catalyst with enhanced yields of middle distillates.…”
Section: Future Workmentioning
confidence: 99%